Effect of rake angle and feed rate on tool wear and surface topography for different chip size in machining carbon steels - Mohd Fawzi, Zamri; Ahmad Razlan, Yusoff (Malaysian Tribology Society (MYTRIBOS), 2022)
This paper proposes tool wear and surface topography analyses in cutting carbon steels 1045 that producing different chip types. The problem of continuous chip due to the different rake angle and feed rate cause the reduction of the surface quality and tool life. The cutting rake angle is set based on the difference angle of shim support for the tool holder. Beside rake angle, different feed rate can improve the surface topography and the tool wear. Tests are carried out using carbon steel 1045 as workpiece material and chip breaker CNMG 120412 as tool insert under dry machining conditions. Results indicated that the lowest the tool wear, the better surface topography produced from the segmented chip at feed rate 0.4 mm/rev and a rake angle −9°. The effect of rake angle and feed rate overcome the problem of continuous chip that associated with low tool wear and surface topography.